Coleridge, philosophy, and religion : Aids to reflection and the mirror of the spirit - Hedley, Douglas (Cambridge University Press, 2008)
Coleridge's relation to his German contemporaries constitutes the toughest problem in assessing his standing as a thinker. For the last half-century this relationship has been described, ultimately, as parasitic. As a result, Coleridge's contribution to religious thought has been seen primarily in terms of his poetic genius. This book revives and deepens the evaluation of Coleridge as a philosophical theologian in his own right. Coleridge had a critical and creative relation to, and kinship with, German Idealism. Moreover, the principal impulse behind his engagement with that philosophy is traced to the more immediate context of English Unitarian-Trinitarian controversy of the eighteenth and nineteenth centuries. The book re-establishes Coleridge as a philosopher of religion and as a vital source for contemporary theological reflection.